2017
DOI: 10.18280/ijht.350101
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of the chaotic flow in three-dimensional open geometry and its effect on the both fluid mixing and heat performances

Abstract: In this study, we investigate the chaotic behavior of fluid particles in three-dimensional open geometries and their effects on the amelioration of miscible fluids mixing, thermal homogenization and thermal performances by using a computational fluid dynamics (CFD) method. Three geometry configurations (straight channel, serpentine-2D channel and chaotic geometry channel serpentine-3D) are considered. The dispersion phenomena are characterized through the presentation of the Poincaré sections and the mixing qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…After analyzing the literature sources, we came to the conclusion that the rate of heat exchange in liquid refrigerants through the laminar boundary layer (LBL) depends on the following main factors: -laminar flow is responsible for the turbulent flow, but is less energy-efficient [2,4]; -LBL, namely its average thickness is responsible for the total thermal resistance of the system [5,6]; -the thermal resistance depends on the coefficient of surface tension of the refrigerant [7]; -the intensity of heat exchange depends on the hydrophilicity or hydrophobicity of the wetting surface [8];…”
Section: Problem Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…After analyzing the literature sources, we came to the conclusion that the rate of heat exchange in liquid refrigerants through the laminar boundary layer (LBL) depends on the following main factors: -laminar flow is responsible for the turbulent flow, but is less energy-efficient [2,4]; -LBL, namely its average thickness is responsible for the total thermal resistance of the system [5,6]; -the thermal resistance depends on the coefficient of surface tension of the refrigerant [7]; -the intensity of heat exchange depends on the hydrophilicity or hydrophobicity of the wetting surface [8];…”
Section: Problem Formulationmentioning
confidence: 99%
“…To increase the heat transfer coefficients in heat exchangers, various methods are used, in particular, the modification of the structural elements of boilers and other equipment [1], the increase in the turbulence of the refrigerant flows [2], the use of liquids with the optimal concentration of surfactants (SAS). For example, the maximum rate of heat exchange was observed when a nonionic surfactant was added to water [3].…”
Section: Introduktionmentioning
confidence: 99%
“…It was found that the mixing of the materials in the channel was facilitated by the chaotic advection generated in the C‐shaped channel, and the distribution of the material in the channel was thus more uniform. Boukhalkhal et al [ 22 ] compared numerically the effect of geometry configurations (straight channel, serpentine 2D channel, and chaotic geometry channel serpentine‐3D) and the results showed that height capacities in terms of mixing and heat performances are obtained by the chaotic geometry. Moreno‐Blanco et al [ 23 ] analyzed the overpotentials inherent during the operation of a SOFC and found the performance of SOFC is affected by the ratio between the gas channel–electrode interface area and the active area.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have investigated several aspects of the convective flow problems under different flow conditions [4]. However, all the studies above are limited to the Newtonian case in which the classical Navier -Stokes equation is valid [5]. Ambethkar and Kumar [6] used the stream function-vorticity formulation to solve the governing equations of 2-D unsteady viscous incompressible flow along with no-slip and slip wall boundary conditions.…”
Section: Introductionmentioning
confidence: 99%